Managing English Language Instruction: Private Teachers' Strategies for Enhancing Students' Speaking Skills - Handriyan, Deden Fery; Sabarun, Sabarun; Mirza, Akhmad Ali (Journal of Educational Management Research, 2025)
This study examines the strategies employed by private English tutors in Indonesia to enhance students' speaking skills, particularly in non-formal educational settings. English speaking proficiency is crucial for academic and professional success, yet many students face barriers such as anxiety, lack of confidence, and limited practice opportunities. The study aims to explore the methods used by private tutors to address these challenges and improve speaking competence. Using a qualitative case study approach, data were collected through semi-structured interviews with five experienced private tutors in Palangka Raya. The findings reveal that tutors utilize communicative strategies such as role-playing, storytelling, task-based learning, and digital tools to foster student engagement and fluency. Additionally, tutors adapt their approaches to meet individual student needs, addressing psychological factors like anxiety and motivation. The study contributes to the understanding of private tutoring practices, emphasizing the importance of creativity and flexibility in non-formal English language instruction. The findings suggest the need for further recognition of private tutoring as an essential component of language education in Indonesia.